A review on contribution of Leguminous Cover Crop (LCC) in cropping lands / Wan Nur Fatin Iezyan Wan Ilias - Wan Ilias, Wan Nur Fatin Iezyan (Faculty of Plantation and Agrotechnology, 2017)
Legume cover crops (LCCs) are established and maintained in the plantations for conserving soil and improving soil structure and fertility. They are creepers, easy to establish and play important role in nitrogen (N) fixation by root nodulation. During N-fixation, the symbiosis occurs between leguminous root and Rhizobium. LCCs are the most desirable plants to serve as groundcovers in plantations. They vary widely in their ability to prevent erosion, suppress weeds and increase organic matters in the soil. The major contribution of LCCs is fixing the atmospheric N for use by subsequent crops and helps to decrease the dependence on external input for example fertilizer. The common LCCs established in estates are Mucuna bracteata, Pueraria phaseoloides, Calapogonium mucunoides and Centrosema pubescens. LCC seeds are planted as soon as possible so that a good surface coverage is obtained and this quickly reduces silting of the terraces.